A Procedure for Entering into a Public-Private Partnership (Lex localis - Journal of Local Self-Government, 2009)
The prescribed procedure for entering into a public-private partnership, which is the research subject in this paper, is extremely complex and long-lasting because in addition to the umbrella Public-Private Partnership Act, the public partner must observe also the regulations governing the commercial public services, public procurement, public finance and disposal of the physical assets of the state, regions and municipalities. Due to a great number of regulations that need to be observed upon entering into a public-private partnership, in a given case, the public partner has to judge whether or not it is more economical and appropriate to carry out his intention to finance investments in infrastructure or to carry out public service activities in a different manner either by granting an architectural right or by selling physical assets, or by public procurement and not by entering into a public-private partnership.KEYWORDS: • local self-government • public service • public-private partnership • Slovenia